THE EFFECT OF DIGITAL LITERACY ON STUDENTS’ LEARNING OUTCOMES IN A GEOGRAPHIC INFORMATION SYSTEMS COURSE IN THE ENVIRONMENTAL ENGINEERING STUDY PROGRAM AT UNIVERSITAS HAMZANWADI - Isnein Akbar; Mutia Permata Sari; Agus Muliadi Putra (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid development of information and communication technologies has significantly transformed higher education. Teaching and learning processes are increasingly supported by digital platforms, Learning Management Systems (LMS), and abundant online learning resources. In this context, university students are required to possess adequate digital literacy, particularly in software- and spatial-analysis-based courses such as Geographic Information Systems (GIS), which is a key course in the Environmental Engineering curriculum. This study aimed to analyze the effect of digital literacy on students’ learning outcomes in a GIS course offered in the Environmental Engineering Study Program at Universitas Hamzanwadi. A quantitative approach with a correlational design was employed. The population consisted of students enrolled in the GIS course in the odd semester of the 2024/2025 academic year, and all 44 students were taken as the sample using a saturated sampling technique. Digital literacy was measured using a Likert-scale questionnaire (1–5) covering technical skills, information search and evaluation, information management, online communication and collaboration, and ethical use of digital media, while learning outcomes were obtained from the final course grades. The data analysis showed that the mean score of students’ digital literacy was 3.6 (moderately high), with a standard deviation of 0.45, whereas the mean GIS course grade was 78.5 with a standard deviation of 6.8. Pearson correlation analysis indicated a positive and significant relationship between digital literacy and learning outcomes (r = 0.62; p < 0.01). Simple linear regression further revealed that digital literacy accounted for approximately 38% of the variance in learning outcomes (R² = 0.38), with the regression equation Ŷ = 52.3 + 7.3X. These findings highlight the importance of strengthening students’ digital literacy in GIS instruction through training, project-based assignments, and the optimal utilization of Learning Management Systems.